Banks of automatic capacitors in electrical distribution systems: a hibrid algorithm of control - Alves,Helton do Nascimento (2005)
A microgenetic algorithm (MGA) in conjunction with fuzzy logic (FL) is proposed for solving the capacitor placement problem. The objective function includes economic savings obtained by energy loss reduction and peak power loss reduction in contrast with acquisition and installation costs of fixed and switched capacitors. Voltage constraints are considered. A simple and efficient method for load flow solution is used, with acceptable CPU time, even for very extensive distribution systems under full load. An approximate load-duration curve divided in different load levels is used to compute energy losses. A 104-bus test system is presented and the results are compared to the solution given by another search technique. This comparison confirms the efficiency of the proposed method which makes it promising to solve complex problems of capacitor placement in distribution feeders.